IoT-Based Smart System for Monitoring and Automating Lemongrass Cultivation - Muhammad Dzharfan Alkonso; Mohd Shamian Zainal (Progress in Engineering Application and Technology, 2026)
The development of the IOT project is based on smart monitoring and automation system for lemongrass cultivation to replace conventional manual practices. Traditional farming practices require a constant human involvement, and maintaining uniform for water distribution across all plants is challenging, which may adversely affect crop growth. The system utilizes a capacitive soil moisture sensor, an RS485 type NPK sensor, and ESP32 microcontroller for real time monitoring of automation irrigation and fertilization. Water pumps are activated based on a threshold driven automated and the soil moisture or nutrients level drops under certain values. Cloud integration is enabled with Google Apps Script to log data and create a real time data that display using google sheet. This includes a soil moisture sensor, NPK sensor, two relay modules, 5V DC water pumps, one I2C LCD display and LED indicators. The two pump system discourages running at both pumps in the same time to reduce nutrient dilution and water waste. The system operates for four daily cycles, thus achieves lower power consumption but still effectually monitoring. Field tests showed improvement in efficiency for irrigation, fertilization, less manual labour and enhanced plant growth. The soil moisture sensor performed well in irrigating control and the NPK sensor was able to monitor nutrient concentration with good accuracy but that its response was very sensitive to the varied electric conductivities of soils. Overall, the prototyped IoT solution is a simple yet feasible system that can bring about an affordable and cost effective modern type of agriculture, ideal for small scale farming, potentially enhancing agricultural efficiency and crop productivity by data driven automation.